THE EVER-CONTEMPORARY CHARACTER OF COLOURS AND INTERIOR DECORATION - Vyas, Bhawna (International Journal of Research -GRANTHAALAYAH, 2021)
Colours are, perhaps, as old as the universe is; might be older than that. But, for sure, colours are older than arts and are related to every aspect of human life. A colour gets its identity from the rays it generates. In other words, colours are composed of radiations. Thus, when it is about colours, it is more about science than it is about arts. And science cannot be regional or time-bound; it is always universally and timelessly applicable. This character of colours inspired me to write ‘The Ever-Contemporary Character of Colours and Interior Decoration’ and helped me in taking examples from different periods of history, thus making the research paper interesting. In interior decoration, undoubtedly, line and proportion are the most important elements but it falls to the lot of few to be able to dictate what they desire in these spheres. Most of the people are content to limit their interior decoration activities to colour only, as this can be cheaply applied to the walls and choice of small accessories etc. Moreover, changing the colour also changes the look and ambience of an interior instantly and intensely. It also helps in expressing one’s personality in their interior and these can be easily done with colour. Colour, therefore, plays the major part in decorative schemes.